Efektivitas Program Yaumuna (Layanan Khusus Perempuan Dan Anak) Di Pengadilan Agama Jember - Khoiruddin, Muhammad; Hidayat, Ahmat Taufik (Sekolah Tinggi Agama Islam Miftahul Ulum Lumajang, 2024)
Gender issues seem to have no end. Many emerging topics revolve around gender equality between men and women, particularly in the field of education. In communities that still adhere to patriarchal culture—especially in Prajjan Village, Campolong, Sampang—it is commonly believed that no matter how high a woman’s education is, she will still end up taking care of the kitchen, children, and other domestic matters. This assumption raises an important question for the researcher: how do community leaders view the phenomenon of wives having higher educational attainment than their husbands, and what are the implications for family harmony? This study is an empirical juridical research, aiming to reveal the legal facts concerning the perspectives of community leaders who still embrace patriarchal culture regarding the phenomenon of wives being more highly educated than their husbands and its implications for family harmony. The facts surrounding this phenomenon are analyzed through a gender analysis framework in order to answer the research questions. The findings show that community leaders in Prajjan Village generally do not consider it a problem if a wife has a higher level of education than her husband. However, one informant expressed a different opinion. Furthermore, the study found that educational differences do not affect marital harmony, but issues tend to arise when the wife’s income is higher than the husband’s.